Centripetal Joyce / Joyce Centrifugal - Bénéjam, Valérie,; Conley, Tim,; Slote, Sam, (European Joyce Studies ;, 2025)
In Dublin in June 2022, a symposium of scholars celebrated the centenary of the original publication of Joyce's Ulysses . This volume, a gathering of selected papers presented at that event, displays how vibrant and varied are the avenues of inquiry and research into Joyce's works today. From orality to elegy, contemplating comparisons with artists as different as Ovid, Derek Walcot, and John Cage, these essays project inward (centripetally) and outward (centrifugally) to examine the receptions of Joyce's works, their legacies, and the possible futures of Joyce studies.